Sectoral Volatility, Development, and Governance: A Case Study of Pakistan (The Pakistan Development Review, 2006)
Development of overall economy of any country largely depends upon the characteristics of different prominent sectors such as agriculture, industry, services, etc. Sharp structural change in prominent sectors are experienced by the Pakistan’s economy during the last four decades, in which industrial and service sector have exhibited an extra ordinary rate of growth, while the agricultural sector did not shown that rate of growth which was experienced during the time of green revolution. Due to these structural changes in the prominent sectors volatility of growth rate has been experienced by the economy. To the extent that most of the recent volatility in growth rate of GDP can be attributed to the increasing share of the some volatility of the some prominent sectors, the analysis of their volatility can be useful in providing some enlightenment on the factors behind this phenomenon and its implications for the formulation of the policy in the future.